The reformatory : a novel [compact disc, unabridged] - Due, Tananarive, 1966- (Simon & Schuster Audio, 2023)
Gracetown, Florida, summer 1950. Robert Stephen Jones Jr. is sent to Gracetown School for Boys for kicking a white boy's leg. But the Gracetown School for Boys isn't just any reform school. As Robert finds, it's a segregated school that is haunted from the boys who have died there.